Analisis Faktor-Faktor yang Mempengaruhi Penerapan Berpikir Kritis Perawat dalam Melaksanakan Asuhan Keperawatan di Rumah Sakit - Yanti Sutriyanti; Mulyadi Mulyadi (JURNAL KEPERAWATAN RAFLESIA, 2019)
Critical thinking skills is a very essential ability in providing services to patients. Factors that can influence critical thinking skills include physical condition, motivation, anxiety, habits, intellectual development, consistency, feelings, and experience. These factors can provide positive support or can reduce critical thinking skills. The purpose of the study was to analyze the factors that influence the application of nurses' critical thinking skills in implementing nursing care to patients. Crossectional research design. The study population was inpatient nurses and a total population sample of 113 nurses. The results of this study (73%) were female, (78%) education was not Ners, (91%) were married, (57%) were civil servants, (53%) were more than 30 years old, (58%) were working long < 6 years. There was a significant relationship between sex factors (p. 005), duration of work (p. 0,045), motivation (p. 0.015), anxiety (p. 0.008), intellectual development (p. 001), and experience (0.002) towards the application of critical thinking nurses in implementing nursing care. There was no significant relationship between factors of age, education, marital status, employment status, physical condition, feelings, habits, consistency in the application of nurse critical thinking in implementing nursing care (p value> 0.005).The intellectual development of nurses can improve critical thinking which is the most dominant in implementing nursing care.